Transition-metal sulfides with excellent hydrogen and oxygen reactions: A mini-review - Farhan, Ahmad; Murad, Muhammad; Qayyum, Wajeeha; Nawaz, Aqsa; Sajid, Muhammad; Shahid, Sammia; Qamar, Muhammad Azam (Journal of solid state chemistry, 2024)
In order to create sustainable, environmentally friendly energy systems, the Hydrogen Evolution Reaction and Oxygen Evolution Reaction must be prioritized. Transition metal sulfides (TMSs) have been studied extensively as catalysts for both HER and OER because of their high activity, cheap cost, and availability. However, its low stability and conductivity limit its usefulness. Recent research efforts have focused on developing TMS-based nanocomposites, which combine the advantageous properties of TMSs with those of other materials, in order to overcome these concerns. The latest advances in TMS-based nanocomposites for oxygen reduction reaction and hydrogen reduction reaction are outlined in this article. We begin by discussing the broad concepts of HER and OER and the problems of TMSs in these reactions. We have comprehensively addressed the role of Sulfur atoms in electrocatalytic water splitting. We also emphasize the need to improve the contact between TMSs and other materials to enable effective charge transfer. Lastly, we evaluate the performance of TMS-based nanocomposites in HER and OER and compare their activity to that of other cutting-edge catalysts. We also examine the remaining research problems and potential in this subject. TMS-based nanocomposites show significant potential for practical applications of HER and OER in renewable energy systems. [Display omitted] •The article focuses on the development of transition metal sulfide-based nanocomposites for efficient electrocatalytic water splitting to produce hydrogen fuel from water.•This review discusses the basic fundamentals of electrocatalytical water splitting.•The transition metal sulfide-based nanocomposites have great potential for use in electrocatalytic water splitting.•Future perspectives of TMSs as an efficient electrocatalysts are explained in detail.